2018
DOI: 10.1002/aur.1924
|View full text |Cite
|
Sign up to set email alerts
|

Spatial navigation from same and different directions: The role of executive functions, memory and attention in adults with autism spectrum disorder

Abstract: Navigating an environment is difficult for people with ASD independent of whether they are travelling in the same or in a different direction from that which they originally studied. The present study suggests that flexibility in alternating travel directions, difficulties in remembering landmarks as well as reduced attention to landmarks while learning a route play a role in the navigation difficulties in ASD. Guidance at route learning might help autistic individuals to improve their ability to navigate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Further data are needed to formulate more definitive hypotheses. We are left with two tentative conclusions, namely that on the one hand undiminished or superior visuospatial abilities have been suggested as being characteristic to ASD (Caron et al, 2004; Edgin & Pennington, 2005) and on the other hand, that the hippocampus—the brain structure involved inter alia in memory for locations (Ekstrom & Ranganath, 2017)—may be impaired in ASD (Lind et al, 2014; Lind, Williams, Raber, Peel, & Bowler, 2013; Ring et al, 2017; Ring, Gaigg, Altgassen, et al, 2018; Ring, Gaigg, de Condappa, et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Further data are needed to formulate more definitive hypotheses. We are left with two tentative conclusions, namely that on the one hand undiminished or superior visuospatial abilities have been suggested as being characteristic to ASD (Caron et al, 2004; Edgin & Pennington, 2005) and on the other hand, that the hippocampus—the brain structure involved inter alia in memory for locations (Ekstrom & Ranganath, 2017)—may be impaired in ASD (Lind et al, 2014; Lind, Williams, Raber, Peel, & Bowler, 2013; Ring et al, 2017; Ring, Gaigg, Altgassen, et al, 2018; Ring, Gaigg, de Condappa, et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, these difficulties were also observed in intellectually high-functioning individuals with ASD (here referred to as HFA), who score within normal ranges on standardized tests of cognitive and language abilities. There is evidence for selective impairments in HFA in spatial working memory ( Lai et al, 2017 ; Wang et al, 2017 ), visual perspective taking ( Pearson et al, 2013 ; Shield et al, 2016 ), binding objects to locations ( Ring et al, 2015 ) and spatial navigation ( Lind et al, 2013 , 2014 ; Ring, Gaigg, de Condappa, et al, 2018 ; Smith, 2015 ). Crucially, acquisition of these skills goes hand in hand with linguistic development and involves the mastery of spatial language, that is, verbal descriptions of spatial relations such as under, to the left of, north or towards .…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, other studies have suggested that memory for complex visual scenes is more impaired in ASD when participants experience the scene in the third person and an allocentric representation of the scene is necessary compared to the first person [i.e., egocentric;. Allocentric representation has long been considered a signature of hippocampal function [e.g., Lavenex & Banta-Lavenex, 2013], underscoring difficulty with memory mechanisms supported by the hippocampus, although other studies highlight impoverished spontaneous use of landmark cues in ASD [Ring, Gaigg, de Condappa, Wiener, & Bowler, 2018], suggesting that environmental support may at least in part alleviate difficulties with spatial memory in children with ASD. An alternative account of deficits in item-context associative binding is the theory of enhanced perceptual functioning (EPF).…”
Section: Discussionmentioning
confidence: 99%